Underinsurance in Malaysia: the application of the Monte Carlo simulation - Hendon Redzuan,; Rubayah Yakob,; Zaidi Isa, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study seeks to estimate the extent of underinsurance among Malaysian families in 2012. Underinsurance is quantified by the extent to which the citizens in a country are inadequately covered by the life insurance protection. To measure underinsurance, we use the concept of the life insurance protection gap as proposed by Swiss Re (2004). The mortality protection gap is the difference between the resources needed and the resources available. The resources needed refer to the resources the surviving dependents require for income replacement, debt repayment and other major expenses. The resources available refer to those resources actually available to the dependents from financial assets, social security and life insurance coverage. The data collected are simulated using the Monte Carlo simulation process. Statistical analysis of the results of the simulation runs indicates that, on average, the extent of underinsurance in Malaysia is about RM500,000 per household.